Atlas of Atherosclerosis and Metabolic Syndrome - Grundy, Scott M.; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
In this updated fifth edition of the Atlas of Atherosclerosis and Metabolic Syndrome (formerly the Atlas of Atherosclerosis), the editors have compiled a comprehensive update on the field of atherosclerosis. This four-color atlas includes detailed legends and extensive reference listings for hundreds of illustrations, algorithms, schematics, and images. This new edition focuses more closely on metabolic syndrome, as well as comprehensively covering many other topics including diabetes and vascular risk, obesity management, dietary concerns, drug treatment, gender and ethnicity differences, and many others. The striking, four-color format combined with the breadth of information it contains make this book an invaluable resource for physicians, cardiologists, and all professionals involved in the study and treatment of atherosclerosis.
Metabolic Syndrome Overview -- Triglyceride Rich Lipoproteins and apolipoprotein B -- Newer Cardiovascular and Metabolic Risk Factor -- Dietary Management -- Drug Management -- Ethnic Differences -- Diabetes and Vascular Risk -- Gender Differences.
Keywords: Medicine; Family medicine; Cardiology; Heart -- Surgery; Medicine & Public Health; Cardiology; Cardiac Surgery; Health Promotion and Disease Prevention; General Practice / Family Medicine; Medicine/Public Health, general